2017
DOI: 10.3390/en10101524
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Properties of Cu3SbSe4 Compounds via Gallium Doping

Abstract: Abstract:In this study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…In the Cu 3 SbSe 4 system, Cu vacancies are easily formed due to the low formation energy and contribute to p -type behavior [ 25 ], which is often observed in other Cu chalcogenides [ 5 ]. Undoped Cu 3 SbSe 4 has been reported as an intrinsic semiconductor with a carrier concentration of ~10 18 cm −3 [ 5 , 6 , 7 , 26 ]. The carrier mobility values were 35–62 cm 2 V −1 s −1 , which decreased slightly with increasing HP temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Cu 3 SbSe 4 system, Cu vacancies are easily formed due to the low formation energy and contribute to p -type behavior [ 25 ], which is often observed in other Cu chalcogenides [ 5 ]. Undoped Cu 3 SbSe 4 has been reported as an intrinsic semiconductor with a carrier concentration of ~10 18 cm −3 [ 5 , 6 , 7 , 26 ]. The carrier mobility values were 35–62 cm 2 V −1 s −1 , which decreased slightly with increasing HP temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivities for all the specimens were (2.55–5.71) × 10 3 S m −1 at 323 K and (3.66–4.87) × 10 3 S m −1 at 623 K, indicating a low temperature dependence. Wei et al [ 6 ] obtained 4.7 × 10 3 S m −1 at 323 K and 9.5 × 10 3 S m −1 at 673 K, exhibiting non-degenerate semiconducting behavior, and Zhao et al [ 7 ] reported 2.3 × 10 3 S m −1 at 323 K and 6.3 × 10 3 S m −1 at 650 K.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. [16][17][18][19][25][26][27][28][29] with temperature. Both P-doped and As-doped Cu3SbSe4 compounds yield similar S values (S = 260 and 286 f/V/K, respectively, at 300 K), which are slightly lower than those calculated for Cu3SbSe4 and Cu3Sb1_^Bi;tSe4 (S « 338 fiV/K at 300 K).…”
Section: Seebeck Coefficientmentioning
confidence: 99%
“…In addition to the effects of the structural design, improvements in ATEG performance can also be obtained by adopting state-of-the-art electronic techniques to maximize power generation in transient behaviors (e.g., maximum power point tracking control [46]). Finally, the ongoing research into new thermoelectric materials is expected to substantially increase the actual values of figure of merit in commercial modules in future years [47,48]. Thus, it is interesting to provide a simple tool to determine the increment of the actual ZT e value in order to have positive fuel savings.…”
Section: Configurations With Maximum Power and Maximum Fuel Economymentioning
confidence: 99%